Pengaruh Prinsip-Prinsip Good Governance Dan Budaya Organisasi Terhadap Kinerja Keuangan Lembaga Perkreditan Desa Kota Denpasar - Anggayana, I Putu Novan; Wirajaya, I Gde Ary (E-Jurnal Akuntansi; Vol 29 No 1 (2019)DO - 10.24843/EJA.2019.v29.i01.p21, 2019)
The application of the principles of good governance and organizational culture is very important in managing the organization. The purpose of this study was to determine the effect of the principles of good governance and organizational culture on the financial performance of the Denpasar City Credit Institution (LPD). This research uses a quantitative approach using primary data. The population in this study were all LPDs in Denpasar City as many as 35 LPDs. The sampling method used in this research is the saturated sample method so that the entire population is sampled. The analysis technique used is multiple linear regression. Based on the results of the analysis note that the principles of good governance consisting of transparency, accountability, responsibility, independence and equality simultaneously have a positive effect on financial performance. While organizational culture has no effect on financial performance. Keywords : Good Governance; Organizational Culture; Financial Performance.